MANAJEMEN PRODUKSI SERIAL ANIMASI 3D-LIVE SHOOT AKSI DIDI TIKUS Studi Kasus Produksi Serial Animasi 3D Aksi Didi Tikus oleh PixelEfekt untuk MNCTV - , NUANSA INTIFADA ARYANI; , Ardian Indro Yuwono, SIP, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed to reveal the management of 3D animation series run by an animation studio, in terms of its production process for television. The writer was considering the fact that the appearance of such program is quite rare in Indonesian television. In the meantime, the information about how to manage the local animation series, as well as its production is very limited in the society. The object of this research is the 3D-live shoot Aksi Didi Tikus animation series which is broadcasted by MNCTV. The series is produced by an animation studio called PixelEfekt. As a pioneer of local animation series which has different production process from other animation series in television, this research is mainly focused on the management plan in which the team of Aksi Didi Tikus is using in every production step of its series. The research method of this research is the descriptive method, using a case study of management production of Aksi Didi Tikus animation series. By using the aforementioned method, the research material become limited, hence it was easier for the writer to describe the focus of problem. During the research, the writer interviewed the animation experts as the informants, did the direct observation to the field of research, and did the literature study. The writer aimed to dig deeper on the works of animation industry in Indonesia and the management of animation studio as well. Based on the research result, the management in production process of Aksi Didi Tikus animation series is already in line with the four management function and production procedure of animation series. However, in its application the production results have not yet effective and efficient. It is on the writerâs best interest to make this research a useful additional reference and a little contribution for the study of management production of animation series for television, as well as to give more understanding about the world of animation in Indonesia.